2003
DOI: 10.1634/stemcells.21-2-190
|View full text |Cite
|
Sign up to set email alerts
|

Multipotential Mesenchymal Stem Cells from Femoral Bone Marrow Near the Site of Osteonecrosis

Abstract: Stem cell-based therapies for degenerative disorders and injuries are promising in the new era. Multipotential mesenchymal stem cells (MSCs) from bone marrow (BM) are on the leading edge because they are easy to expand in culture while maintaining their multilineage potential. In vitro assessment of the chondrogenic and osteogenic potentials of cultured MSCs has been established, and the BM used in those experiments was exclusively from healthy donors via iliac crest aspiration. It is unknown whether human mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 39 publications
2
74
0
1
Order By: Relevance
“…Recent results have given evidence of aging in marrow stromal progenitor cells [10,[40][41][42][43][44][45][46]. Other reports demonstrated that osteogenic progenitor cells were maintained during aging [47][48][49]. The question of changes in the osteoprogenitor cell population with age is further complicated by the possibility of sex-dependent differences [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have given evidence of aging in marrow stromal progenitor cells [10,[40][41][42][43][44][45][46]. Other reports demonstrated that osteogenic progenitor cells were maintained during aging [47][48][49]. The question of changes in the osteoprogenitor cell population with age is further complicated by the possibility of sex-dependent differences [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and expansion of human bone marrow mesenchymal stem cells Human bone marrow mesenchymal stem cells were extracted from the trabecular bone in the femoral head of patients after total hip arthroplasty, as described elsewhere with some modifications (Schutze et al 2005;Lee et al 2003;Sakaguchi et al 2004;Quiroz et al 2008). The protocol was approved by the Review Boards of the Hospital Pablo Tobo´n Uribe and the CES University, and all samples were processed after written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…zymed.com). In vitro osteogenic, adipogenic, and chondrogenic assays were done as previously reported [13,14].…”
Section: Mouse Bmmsc Culturementioning
confidence: 99%